Tool for Self-Discovery: Guiding College Career Choice through Skills - Juárez López, Kevin José (2025)
The research focuses on developing and applying a self-discovery tool to help students choose their college careers, based on the analysis of their skills. This approach addresses the common problem of inappropriate career choices, which can result in academic and career dissatisfaction, so the goal of this tool is to offer meaningful support in this complicated decision. The study highlights the need for a system that considers both vocational interests and a detailed assessment of personal skills. Using a mixed methodology involving surveys, interviews and data analysis, the effectiveness of the tool is evaluated in a variety of educational contexts. This mixed methodology allows for a more accurate assessment of the impact of the tool, giving the possibility to observe how the tool influences students’ career choice decision making. The tool uses a questionnaire to identify key skills in areas such as logic, creativity, communication and teamwork, generating personalized career recommendations. Preliminary results show that students who used the tool have greater clarity and confidence in their academic decisions, with fewer career changes and greater satisfaction. The research concludes that a skills-based tool is valuable in guiding students in their academic and career decisions, this tool can be significant for students to choose the right path for their interests, but also increase their potential and satisfaction.